The distinct contribution of sternotomy to the systemic inflammatory response during children's heart surgery - Bierer, Joel David; Paffile, Julia; Stanzel, Roger; Henderson, Mark; Sapp, John; Andreou, Pantelis; Marshall, Jean Sylvia; Horne, David (Frontiers in Immunology, 2026)
BackgroundSternotomy provides access to the mediastinum, heart and great vessels for congenital cardiac surgery in children. The contribution of this incision to the systemic inflammatory response during open-heart surgery, particularly in combination with the complement-mediated response to cardiopulmonary bypass (CPB), is unknown. This study aimed to characterize the inflammatory mediator profile of sternotomy and contrast that with CPB-associated inflammation.MethodsThis study is a post-hoc analysis of a single-arm prospective clinical study (NCT05154864) of 40 pediatric patients undergoing congenital cardiac surgery with CPB. Arterial blood samples were taken before and after sternotomy, but before CPB initiation (sternotomy phase), and after CPB exposure (CPB phase). Thirty-three inflammatory mediators from the cytokine, chemokine, complement, and adhesion molecule families were measured. The mediator changes were calculated for each phase and described using median fold changes. A principal component analysis with hierarchical clustering (PCA-HCPC) was conducted on mediator changes over the sternotomy phase.ResultsCompared to baseline, all 16 cytokines and chemokines assessed increased through the sternotomy phase, while complement and adhesion molecules were static or decreased. The most active mediators were IL-1β (3.3x median fold increase), CXCL2 (3.3x), IL-6 (2.6x), IL-10 (2.6x), GM-CSF (2.3x), IL-1α (2.2x) and IL-2 (1.7x). The PCA-HCPC showed three statistically significant clusters, cluster 1 grouped cytokines and chemokines with the sternotomy phase, while complement mediators and adhesion molecules were in separate clusters. In contrast to the CPB exposure, sternotomy showed a predominant contribution of TNF, IL-1α, IL-1β, IL-2, TRAIL, CCL3, CCL4, CXCL1, CXCL2 and GM-CSF to the systemic inflammatory response.ConclusionsSternotomy and related tissue trauma produce a distinct systemic inflammatory mediator profile, consisting of pro-inflammatory cytokines and chemokines but not complement. The mediators IL-6, CXCL8, IL-1Ra and IL-10 are sequentially induced by both sternotomy and CPB, representing sequential immunologic stimulation during the cardiac operation.